(untitled) (Applied Biological Research, 2024)
Rivers are important source of fresh water which is important for the sustenance and welfare of the society. The present study deals with the assessment of water quality parameters and with the population of phyto- and zoo-plankton of Himalayan Bhagirathi river in Uttarkashi, Uttarakhand (India). The samples were collected from the study area during summer, monsoon, and winter seasons for water quality and phyto- and zoo-plankton analysis. The air temperature, depth temperature, pH, total alkalinity, total dissolved solids (TDS), dissolved oxygen (DO), turbidity, free CO2, electric conductivity (EC), biological oxygen demand (BOD) and total hardness were determined. The study revealed that DO was maximum in winter (12.35 ± 0.25 mg L-1) and minimum in June to September (9.75 ± 0.25 mg L-1). The Bhagirathi water contained maximum DO in colder month, followed by a gradual decrease to its lowest value during June to September. BOD, an important indicator of pollution status of a water body, was high during summer perhaps due to low discharge at river. BOD was high in monsoon (4.4 ± 0.14 mg L-1) and low in winter (1.5 ± 0.14 mg L-1). The study revealed low river flow during winter. Bacillariophyceae was maximum (442 units L-1) in February and minimum (18 units L-1) in July. Chlorophyceae was maximum (80 units L-1) in January and minimum (6 units L-1) in August, while Myxophyceaewas maximum (34 units L-1) in February and minimum in June and Xanthophyceae was not recorded at this site. The maximum number of zooplankton genera was observed during winter and minimum in rainy season. The study showed that there is an urgent need to have proper water management in rainy and summer seasons so as to restore the water quality of this river.